Association of cleft lip and/or palate in people born to consanguineous parents: A 13-year retrospective study from a very high-volume cleft center - Praveen Kumar Neela; Srinivas Gosla Reddy; Akhter Husain; Vasavi Mohan (Wolters Kluwer Medknow Publications, 2019)
Objective: The objective of this study was to investigate the association of cleft lip (CL) and/or cleft palate (CP) in people born to consanguineous parents. Methodology: This retrospective study was conducted at GSR Institute of Craniofacial Surgery, Hyderabad, a very high-volume cleft center. Medical records of 18,242 cleft patients who came for treatment in the past 13 years were physically searched for the presence of consanguinity of their parents. About 3653 patients' case records were identified. Then, the data related to gender, type of cleft, degree of consanguinity, presence of positive family history were collected from these 3653 patients' records and entered in Microsoft Excel which was later sent for statistical analysis. Results: Distribution of study participants according to various study variables such as gender, type of cleft, and degree of consanguinity showed interesting findings. Almost 20.02% of the total 18,242 cleft patients' records showed consanguinity of their parents. Nearly 96.7% of patients had CL. CP was seen in 73.7% of patients. About 57.8% of parents had the first degree of consanguinity. Only 3.5% had a positive family history. Chi-square test showed that there was a significant difference in the distribution of patients according to degree of consanguinity and CL, variations in CL and gender, cleft alveolus and gender, degree of consanguinity and CL. Conclusion: Consanguinity is a major etiological factor in CL and/or CP.